Feasibility Study Program Zakat Community Development Studi Kasus: Desa Mekarsari, Kabupaten Garut - Elis Nurhasanah (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2019)
Abstract. Feasibility Study of Zakat Community Development Programs Case Study: Mekarsari, Garut. This paper assessed the feasibility of community-based zakat (zakat community development) recipients and proposing relevant empowerment programs to alleviate mustahiq community conditions in Mekarsari Village, Garut District. Assessment tool used in this research adopted by Puskas BAZNAS was Zakat Village Index (IDZ). Result showed that Mekarsari Village reached 0.55, with the score of economic dimension index reached 0.39, 0.54 for the health dimension, 0.64 for the education deimension, social and humanitarian dimension and da’wah dimension are 0.55, 0.68 respectively. Thus, Mekarsari Village in Garut District cauld be considered for assistance by zakat fund based on calculation of IDZ. The empowerment program relevant to the condition of the mustahiq community in Garut District was community economic improvement through empowerment of economic potential owned based on consideration of the value of the economic dimension had the lowest value of the five IDZ variable. Abstrak. Feasibility Study Program Zakat Community Development Studi Kasus: Desa Mekarsari, Kabupaten Garut. Artikel ini bertujuan mengukur kelayakan mustahik berbasis komunitas (Zakat community development) dan mengusulkan program pemberdayaan yang relevan untuk mengurangi kondisi komunitas mustahik di Desa Mekarsari, Kabupaten Garut. Alat ukur yang digunakan dalam penelitian ini diadopsi dari Puskas BAZNAS yaitu Indeks Desa Zakat. Hasil menunjukan bahwa Desa Mekarsari memiliki nilai IDZ 0.55, dengan nilai dimensi ekonomi 0.39, 0.54 nilai dimensi kesehatan, 0.64 nilai dimensi pendidikan, dimensi sosial dan kemanusiaan serta dakwah masing masing dengan nilai 0.55, 0.68. Dengan demikian, Desa Mekarsari di Kabupaten Garut dapat dipertimbangakan utnutk dibantu oleh dana zakat berdasarkan hasil perhitungan IDZ. Program yang relevan dengan kondisi komunitas mustahik di Desa mekarsari adalah meningkatkan ekonomi komunitas melalui pemberdayaan potensi ekonomi yang dimiliki berdasar pada pertimbangan nilai dimensi ekonomi yang memiliki nilai terendah dari kelima variabel IDZ.